THE EFFECT OF MOTIVATION OF PADDY STRAW MUSHROOM (Volvariella volvaceae) FARMER IN INCREASING THE INCOME OF PADDY STRAW MUSHROOM INDUSTRY IN JEMBER - Nurul Fathiyah Fauzi (UNEJ e-Proceeding, 2012)
In Jember, paddy straw mushroom industry has reached in 17 region consisting 123 farmer. Mainly, it become a main occupation of farmer. So, it shows amount af farmers aremotivated to cultivate paddy straw mushroom with many obstacles and opportunity toincrease maximal income. Indicator of motivation itself is fulfillment of requirement,natural resouces, labour, the available of means production, the goverment attention,revenue, and market demand. The methodology of sampling is by using Cluster Samplingand Incidental Sampling. In methodology of data analysis, researcher uses PATH analysisand FFA analysis by using primer and secondary data. The result of research shows (1)effect of sosial factors to the motivation of paddy straw mushroom farmers affects themotivation. It is include the easy of cultivation factor, capital, available of meansproduction, and market demand. Whereas, the effect of motivation to the income throughproduction factor shows positive correlation to the significance of prodduction factor to theincome. (2) The most dominant and effective factor is the easy of cultivation factor toincrease the income of paddy straw mushroom industry should be carried out by farmer orgovernment. (3) The main obstacle in paddy straw mushroom industry is H3 and H4 factor.The main opportunity of paddy straw mushroom industry is D2 dan D3 factor. (4) Strategyto increase the income of paddy straw mushroom industry in Jember is by giving the softbureaucracy to gain investment credit through APJMJ, goverment or farmer associated inAPJMJ should increase APJMJ member, and develop the available of means production byincreasing provider unit in achievable place.